PERAN LEMBAGA DAN MASYARAKAT TERHADAP SITUS BUDAYA DI KELURAHAN KAMPUNG BANDAR KECAMATAN SENAPELAN PEKANBARU - Muhammad Badrun; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Social role is an act of a person in a certain way in an effort to exercise the right and obligation which appropriate with the status it has. A social phenomenon that occured in Kelurahan Kampung Bandar , where in the history of this area became the Value History of the birth of Pekanbaru City. The reality is not running as it should be. The lack of management in every historical sites, data collection clearly, the arrangement of the area, and lack of socialization to the community, thus make the public and the local community do not know if the location is part of the history of Pekanbaru City. This research aims to identify the culture site that has been the officially recorded in Kelurahan Kampung Bandar, to explore the local people’s knowledge of the Culture Site, to describe the role of related institute in managing and maintaining the Culture Sites. The theory used is functional structural theory by Talcot Parson. Data analysis was done by qualitative descriptive, tehnique of collecting the data in this research is purposive where the number of respondent is 7 peoples consist of people who joined in Group Sadar Wisata and Institution of Kelurahan Kmapung Bandar Senapelan, the historian of Riau, Lembaga Adat Melayu Riau, Lembaga Adat Melayu Riau Pekanbaru, Kelurahan Kampung Bandar and Tourism Office of Pekanbaru City. From the result of this research in the field that the community (Group Sadar Wisata And Institution of Kelurahan Kampung Bandar Senapelan) have performed its role with the knowledge and ability they have. But not maximally role of the government (Department of Culture and Tourism Pekanbaru City), Community Institution (LAMR Kota Pekanbaru) so that the people in general do not know if the location is part of Culture and history of Pekanbaru City.Key word : Culture Site, Community Knowledge, Institutional Role